Micronucleus assay as biomarker of DNA damage in population exposed to ionizing radiation - Chaves-Campos, Fabio Andrés (2021)
Introduction: Ionizing radiation (IR) is capable of causing DNA damage. For the evaluation of this phenomenon it is possible to use chromosomal aberrations as biomarkers. The “Cytokinesis-Block Micronucleus assay” (CBMN) is a cytogenetic technique that allows to demonstrate the effect of genotoxic agents. Proposition: in the present review, we will describe the molecular mechanisms involved in micronucleus radioinduction, the micronucleus technique and criteria for analysis, its applications within biological research and its extension in clinical research, with emphasis on its application as a biomarker of radioinduced genetic damage. Arguments for discussion: the CBMN is considered a reliable, simple and fast technique and there is evidence of its applicability in the evaluation of biological effects in occupationally exposed personnel and in isolated or large-scale radiological accidents. Conclusions: the CBMN a valuable tool in estimating radiological risk in populations exposed to low doses of IR, allowing to guide decision-making regarding prevention or mitigation of exposure to IR in populations involved. Similarly, the CBMN can be used in research in the field of radiobiology, as a means to describe the effects of ionizing radiation on DNA.